Preventing Stunting in Early Childhood and Its Effects on Educational and Economic Factors - Solehudin, Rd. Heri (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Stunting is an intractable problem. So far, parents' views on stunting are wrong. Parents believe stunted growth is inherited. Lack of growth, development, and other factors cause stunting, not genetics. Stunting is linked to inadequate exclusive breastfeeding and low parental education, especially among mothers. Early stunting indications are often undetected. Parents often view smallness as insignificant. Their children will mature. This project seeks ways to reduce early childhood stunting and its effects on schooling and employment. The research method comprised aA detailed literature survey and meticulous analysis of Miles and Huberman's papers from 2010 to 2018. Essays from a large qualitative systematic literature study were published in top national and international journals. Google Scholar search results for "stunting" and "prevention", "early childhood stunting", "prevention and impact", and "economic education" are analysed. The analysis focuses on "Prevention of Stunting in Early Childhood and its Impact on Educational and Economic Factors." Find accessible scholarly papers with at least 25 citations. These articles should be lengthy and printable. They should evaluate classroom behaviour using descriptive qualitative research. Harzing Publish or Perish retrieves articles. The findings show that most people understand stunting in children. Stunted children need to focus on school, which affects their future. The poor education of undernourished children hinders their labour market success, lowering income and weakening the economy. Posyandu's proven effectiveness in helping women track their kids' growth and development makes it essential. To help women without access to the Posyandu track their children's progress, the community needs a Mobile Posyandu. Village officials, midwives, and posyandu cadres are essential to a stunting-free Indonesia on its development path.